Validation of pretreatment neutrophil–lymphocyte ratio as a prognostic factor in a European cohort of patients with upper tract urothelial carcinoma. (27th November 2013) - Dalpiaz, Orietta; Ehrlich, Georg C.; Mannweiler, Sebastian; Hernández, Jessica M.Martín; Gerger, Armin; Stojakovic, Tatjana; Pummer, Karl; Zigeuner, Richard; Pichler, Martin; Hutterer, Georg C.
<x xml:space="preserve">Abstract</x> Objective To investigate the potential prognostic significance of the neutrophil–lymphocyte ratio (NLR) in a large European cohort of patients with upper urinary tract urothelial cell carcinoma (UUT‐UCC). Patients and Methods We retrospectively evaluated data from 202 consecutive patients with non‐metastatic upper urinary tract urothelial cell carcinoma (UUT‐UCC), who underwent surgery between 1990 and 2012 at a single tertiary academic centre. Patients' cancer‐specific survival (CSS) and overall survival (OS) were assessed using the Kaplan–Meier method. To evaluate the independent prognostic significance of the NLR, multivariate proportional Cox regression models were applied for both endpoints. Results A higher NLR was significantly associated with shorter CSS (P = 0.002, log‐rank test), as well as with shorter OS (P < 0.001, log‐rank test). Multivariate analysis identified a high NLR as an independent prognostic factor for patients' CSS (hazard ratio 2.72, 95% CI 1.25–5.93, P = 0.012), and OS (hazard ratio 2.48, 95% CI 1.31–4.70, P = 0.005). Conclusions In the present cohort, patients with a high preoperative NLR had higher cancer‐specific and overall mortality after radical surgery for UUT‐UCC, compared with those with a low preoperative NLR. This easily identifiable laboratory measure should be considered as an additional prognostic factor in UUT‐UCC in future.